2019
DOI: 10.1021/acs.analchem.9b01862
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Loaded by Rhodamine B As a Novel Chemiluminescence System for the Paper-Based Analytical Devices and Its Application for Total Phenolic Content Determination in Food Samples

Abstract: Herein, a novel paper-based chemiluminescence (CL) device has been reported for the estimation of total phenolic content of food samples. The CL system implemented on the paper was based on a hydrogen peroxide (H 2 O 2 )−rhodamine b (RhoB)−cobalt metal organic framework (CoMOF) reaction. It was found that the reaction of H 2 O 2 with RhoB molecules, loaded into the nanopores of CoMOF (R@CoMOF), can produce an intensive CL emission. The experiments on the paper indicated that in the presence of CoMOF, the CL em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Apart from luminol, rhodamine B (RhB) was recently used as a chemiluminescence substrate for peroxidase mimics (Figure 1c). [ 36 ] The CL spectrum of RhB is the same as that of its fluorescence. In addition, nanozymes have been shown to degrade RhB to a product that has a lower CL yield.…”
Section: Characteristics Of Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from luminol, rhodamine B (RhB) was recently used as a chemiluminescence substrate for peroxidase mimics (Figure 1c). [ 36 ] The CL spectrum of RhB is the same as that of its fluorescence. In addition, nanozymes have been shown to degrade RhB to a product that has a lower CL yield.…”
Section: Characteristics Of Substratesmentioning
confidence: 99%
“…[ 3 ] Some MOFs, especially those containing Fe, Cu, and Co, were reported to have peroxidase‐like activities. [ 36,110–112 ] Similar to other peroxidase nanozymes, a Fenton‐like mechanism with ·OH generation can describe their activities. The Co‐based MOF was found to enhance the CL emission of RhB in the presence of H 2 O 2 , while phenolic antioxidants can significantly inhibit it.…”
Section: Nanozymes For Producing Luminescent Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemiluminescence (CL) [11][12][13] has the advantages of fast speed, simple instrumentation, wide linear range and high sensitivity. [14][15] Therefore, CL analysis has been widely used in diverse fields including biology, food analysis, 16 pharmacology 17 and clinical assays. 18 In recent years, CL has been used for the detection of PCs and the evaluation of antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Although these CL reactions were simple and these agents were easy to obtain, the sensitivity for antioxidants was still low. In 2019, Lawati's research group 16 reported that a new H2O2-B (RhoB)-CoMOF CL system for PCs detection on the paper-based device. With RhoB @CoMOF loaded on paper, PC can be sensitively detected in food samples.…”
Section: Introductionmentioning
confidence: 99%